Employee Performance and Talent Management Impact Increasing Construction Company Productivity - Primadi Susanto; Ni Nyoman Sawitri; Hapzi Ali; Zahara Tussoleha Rony (International Journal of Psychology and Health Science, 2023)
Abstract: Purpose – To provide evidence of whether existing variables have indeed been implemented in the findings of existing literature from various online journals, the above problems are a problem in construction companies related to variables. Design/methodology/approach – Qualitative method by searching literature related to variables in this paper that have been implemented from the findings of the paper. Findings – This paper provides color with its qualitative method with existing variables and adds to the repertoire and participation in science and knowledge, especially in the field of human resources with the object of research in construction companies. There is one finding that is the same as the variables of this paper and the same object as the results of certain HR management practices improve employee productivity and performance in construction companies. The results of this paper also corroborate and provide recommendations for other researchers to continue this research. Originality/value – Qualitative papers corroborate existing research results with the same variables and the same objects with different research methods, and also provide treasures and colors in research results, especially in the field of human resources.